Crystalline silica-induced proinflammatory eicosanoid storm in novel alveolar macrophage model quelled by docosahexaenoic acid supplementation - Favor, Olivia K.; Rajasinghe, Lichchavi D.; Wierenga, Kathryn A.; Maddipati, Krishna R.; Lee, Kin Sing Stephen; Olive, Andrew J.; Pestka, James J. (Frontiers in Immunology, 2023)
Introduction Phagocytosis of inhaled crystalline silica (cSiO2) particles by tissue-resident alveolar macrophages (AMs) initiates generation of proinflammatory eicosanoids derived from the ω-6 polyunsaturated fatty acid (PUFA) arachidonic acid (ARA) that contribute to chronic inflammatory disease in the lung. While supplementation with the ω-3 PUFA docosahexaenoic acid (DHA) may influence injurious cSiO2-triggered oxylipin responses, in vitro investigation of this hypothesis in physiologically relevant AMs is challenging due to their short-lived nature and low recovery numbers from mouse lungs. To overcome these challenges, we employed fetal liver-derived alveolar-like macrophages (FLAMs), a self-renewing surrogate that is phenotypically representative of primary lung AMs, to discern how DHA influences cSiO2-induced eicosanoids. Methods We first compared how delivery of 25 µM DHA as ethanolic suspensions or as bovine serum albumin (BSA) complexes to C57BL/6 FLAMs impacts phospholipid fatty acid content. We subsequently treated FLAMs with 25 µM ethanolic DHA or ethanol vehicle (VEH) for 24 h, with or without LPS priming for 2 h, and with or without cSiO2 for 1.5 or 4 h and then measured oxylipin production by LC-MS lipidomics targeting for 156 oxylipins. Results were further related to concurrent proinflammatory cytokine production and cell death induction. Results DHA delivery as ethanolic suspensions or BSA complexes were similarly effective at increasing ω-3 PUFA content of phospholipids while decreasing the ω-6 PUFA arachidonic acid (ARA) and the ω-9 monounsaturated fatty acid oleic acid. cSiO2 time-dependently elicited myriad ARA-derived eicosanoids consisting of prostaglandins, leukotrienes, thromboxanes, and hydroxyeicosatetraenoic acids in unprimed and LPS-primed FLAMs. This cSiO2-induced eicosanoid storm was dramatically suppressed in DHA-supplemented FLAMs which instead produced potentially pro-resolving DHA-derived docosanoids. cSiO2 elicited marked IL-1α, IL-1β, and TNF-α release after 1.5 and 4 h of cSiO2 exposure in LPS-primed FLAMs which was significantly inhibited by DHA. DHA did not affect cSiO2-triggered death induction in unprimed FLAMs but modestly enhanced it in LPS-primed FLAMs. Discussion FLAMs are amenable to lipidome modulation by DHA which suppresses cSiO2-triggered production of ARA-derived eicosanoids and proinflammatory cytokines. FLAMs are a potential in vitro alternative to primary AMs for investigating interventions against early toxicant-triggered inflammation in the lung.